The Importance of Leadership on Business Ethics at Organizations - Dervishi, Aferdita (European Journal of Economics and Business Studies, 2020)
The purpose of this paper is to board the issues dealing with the ethics code of behave, and the role of leadership on motivation of staff to lead up the effectiveness and quality work at organization. The paper presents ethic standards and their importance for the success and competitive priorities for organizations and institutions. The elaboration of paper is carried using normative and comparative method attended by secondary source of data in the form of papers, journals, books, web-pages and manuals of organizations. There are studied principles of the Code of Ethics in two organizations, Bus Eirenann of Ireland and Kosovo Privatization Agency of the Republic of Kosovo, handling the practical implementation of ethic codes in both cases. Next to written policies for ethics there exist failures and mistakes on the ethics at working place that is present in everyday life as a result of improper behave of someone. Ethic behaves have had the positive impact at organizations, while non-ethic behaves have serious impact on the development of staff and it keeps away incitement of tacit knowledge, obstructs innovations and creative work. Development and approval of ethic code and ethic practices at organization will not stop non-ethic behaves, but will give to people a kind of measurement versus which behave may be measured. Executive leaders at organizations and institutions should assess if the written or unwritten code is not respected so that the employees to feel safe for their integrity and appreciated.